influence of heat treatment on the properties of shape memory fibers. II. Tensile properties, dimensional stability, recovery force relaxation, and thermomechanical cyclic properties - Meng, Qinghao; Hu, Jinlian; Yeung, Lap Yan; Hu, Yang (Journal of applied polymer science, 2009)
Shape memory fibers (SMFs) were prepared via a melt spinning process. The fibers were subject to different heat treatments to eliminate internal stress and structure deficiency caused during the melt spinning process. The influences of heat treatments on the SMF thermal properties, molecular orientation, tensile properties, dimensional stability, recovery force relaxation, and thermomechanical cyclic properties were studied. It was found that the heat treatments increased soft segment crystallinity and phase separation while decreased molecular orientation. The low-temperature heat treatment increased the breaking elongation, shape fixity ratios, and decreased boiling water shrinkage while shape recovery ratios were decreased. High-temperature treatment increased both the shape recovery ratios, fixity ratios, recovery stress stability and at the same time decreasing the fiber mechanical strength. The results from differential scanning calorimetry, molecular orientation apparatus, and cyclic tensile testing were used to illustrate the mechanism governing the mechanical properties and shape memory effect. To obtain comprehensive outstanding properties, the SMF is expected to be treated at a high temperature because of the hard segment high glass transition temperature. Unfortunately, the heat treatment could not be conducted at a too high temperature because the SMF became too tacky and soft due to the melting of the soft segment phase.